And After Landing Wrong? - Lomanno, Mark (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
Mark Lomanno reflects on the impact of Ajay Heble's work—especially the book "Landing on the Wrong Note"—on his life and career.